Development of A High Pressure Compressed Natural Gas Mixer for A 1.5 Litre CNG-Diesel Dual Engine - M. M., Noor; K., Kadirgama; D., Ramasamy; M. R. M., Rejab; N. M. Zuki, N. M. (2008)

(untitled)
The Computational Fluid Dynamics (CFD) analysis software was used to study the flow behaviour of compressed natural gas (CNG) and air in a CNG-air mixer to be introduced through the air inlet of a CNG-Diesel dual fuel stationary engine. The results of the simulation show that the Venturi mixer with more holes gives superior engine performance compared to the 4-hole Venturi mixer. Further analysis is done on the different holes mixer to investigate the effect of engine speed on the mass flow rate of CNG and the equivalence ratio Lambda. The second part of the paper represents a comparison results between the performances of a single cylinder research Compression Ignition CI engine fuelled with CNG-diesel system and conventional CI engine fuelled by conventional diesel. The engine was equipped with the simulated Venturi mixer, the result showed significant reduction in the exhaust gas emission compared to the conventional diesel engine. The average power output generated by dual fuel engine was slightly higher than that diesel one at different engine speeds.